Bacterial susceptibility patterns to cotrimoxazole in urinary tract infections of outpatients and inpatients in Jakarta, Indonesia (Faculty of Medicine Universitas Indonesia, 2020)
BACKGROUND Cotrimoxazole, which has been one of the drugs of choice for urinary tract infections (UTIs) since 1960, must be evaluated to determine whether it is still a relevant drug for this use. This study aimed to assess the susceptibility patterns to cotrimoxazole of the bacteria that cause UTIs from urine samples of female outpatients (community-acquired [CA]-UTI) and inpatients (hospital-acquired [HA]-UTI) in Jakarta. METHODS This study was conducted from December 2014 to December 2015. Susceptibility testing of bacteria causing UTIs was conducted on 27 of 311 female outpatient urine samples collected from six clinics in Jakarta, and secondary data susceptibility testing was performed on 27 of 107 urine samples of inpatients from hospitals in Jakarta. These samples were examined in the Clinical Microbiology Laboratory, Faculty of Medicine, Universitas Indonesia, Cipto Mangunkusumo Hospital. RESULTS Susceptibility to cotrimoxazole was reported in 83% of the bacteria causing UTIs in CA-UTI and 44% of the bacteria in HA-UTI patients. Klebsiella pneumoniae was the most common cause of CA-UTI, with all isolates susceptible to cotrimoxazole (100%). Conversely, Escherichia coli was the most common cause of HA-UTI but was only susceptible in some isolates (44%). Bacteria from CA-UTI patients were almost twice as susceptible to cotrimoxazole compared with HA-UTI patients (p = 0.003). CONCLUSIONS Based on the susceptibility patterns identified, cotrimoxazole can be used as a treatment for CA-UTI but not for HA-UTI patients in Jakarta, Indonesia.